Marine tourism development strategy as a main priority in sanur tourism area - Ni Wayan Maryuni Erawati; I Wayan Kiki Sanjaya; Putu Sabda Jayendra (Enrichment : Journal of Management, 2023)
This research will examine fwhat factors attract tourists to carry out marine tourism activities in the Sanur Tourism Area. Using a qualitative approach, which in this study also intends to understand the phenomenon that actually occurs in increasing tourist visits with marketing strategies in Sanur. Selection of informants is based on position, knowledge possessed and data obtained from sources by describing phenomena related to the topic. In research using purposive sampling method. Where the results of this study are empirical reality showing that the tourism object in the Sanur area as a tourist resort still has a charismatic attraction (taksu) for all visitors from the homeland (archipelago tourists) and visitors from all over the world (foreign tourists). Attraction Factors, Amenities